Production of Bioplastic by Local Strains of Bacillus subtilis using Watermelon Peels as Substrate - Musa, B.; Ado, S.A.; Joseph, G.L.; Hussain, I.M.; Sulaiman, M.A.; Tijjani, M.B.; Charanchi, A.S. (UMYU Journal of Microbiology Research)
The amount of environmental contamination brought on by the careless disposal of plastic garbage has increased to 400 million tons every year on a global scale. These synthetically generated traditional polymers are not easily biodegradable. This work was therefore undertaken to isolate Bacillus subtilis from soil with potential to produce bioplastic: Poly-ß-hydroxybutyrate (PHB). Samples of soil were collected from various locations (BG = Botanical Garden, FARD = Fine Art Refuse Dumpsite, SHRD = Suleiman Hall Refuse Dumpsite, FVM = Faculty of Veterinary Medicine animal paddock) within Ahmadu Bello University, Zaria, Nigeria. Spread plate technique was used to isolate B. subtilis on nutrient agar, and the isolates' cultural, morphological, and biochemical properties were identified. The isolates of B. subtilis were screened for PHB production using two different methods: the plate assay method and slide technique using Sudan black B dye. The PHB was then produced using submerged fermentation with watermelon peel as sole source of carbon in the production medium. The PHB was extracted using Sodium-hypochlorite method and the quality of the PHB was determined using FT-IR analysis. Four isolates of Bacillus subtilis were obtained from the soil samples (50 %), one each out of the two samples (50 %) per unit location (BG2, FARD3, SHRD2, and FVM4). The screening revealed that all the isolates were PHB producers. The B. subtilis isolate SHRD2 from the students’ dormitory was found to produce the highest PHB yield of 0.98 g/L from the watermelon substrate, whereas isolate from the animal paddock (FVM4) yielded the lowest quantity of the PHB (0.12 g /L). The biopolymer's (bioplastic) identity was confirmed to be PHB based on the peaks in the FT-IR spectra, which displayed wave numbers for a variety of functional groups, including -O-H, C-H, C-O, and C=O. It was concluded that the local isolates of B. subtilis have potentials for PHB production using watermelon peels as source of carbon and energy.